Changing antibiotic resistance profile of Staphylococcus aureus isolated from HIV patients (2012-2017) in Southern India - Ravichandran Swathirajan Chinnambedu; Ragavan Rameshkumar Marimuthu; Suhas Solomon Sunil; Pradeep Amrose; Vignesh Ramachandran; Balakrishnan Pachamuthu (Elsevier, 2020)
Purpose: Emergence of multidrug-resistant and methicillin-resistant Staphylococcus aureus (MRSA) infections in HIV patients limit the treatment options and challenge the clinical management of infections. The periodic monitoring of S. aureus infections and its drug resistance profile in HIV patients are of paramount importance in clinical management. Materials and methods: A total of 7204 clinical specimens from HIV patients from 2012 to 2017 were processed for the isolation of S. aureus strains using conventional culture techniques and cultures were identified using standard biochemical test. Antibiotic susceptibility of S. aureus strains was tested by Kirby-Bauer disk diffusion method. Results: A total of 380 (5.3%) S. aureus strains were isolated from HIV patients in the study period. High percentage of S. aureus strains were isolates from urine (69.5%) specimen and 58.4% of S. aureus infections were noted among hospitalized patients. Antibiotic susceptibility profile reveals S. aureus was highly resistant to penicillin (95.2%) followed by cephalexin (84.6%). Methicillin resistance was highly observed in the year 2017 (86%) and the rate of MRSA steadily increasing from 51.8% in 2012 to 86% in 2017. Significant increase of S. aureus infections (35%; p < 0.001) and MRSA (76%; p = 0.0007) were observed in the year 2016. Conclusions: This study reports the increasing trends of S. aureus infections and MRSA among HIV patients from Southern India. Multidrug-resistance profile of S. aureus could complicate the selection of proper antibiotic regimens and time cure of HIV patients. Keywords: Methicillin-resistant, Staphylococcus aureus, HIV patients, oxacillin, penicillin